2013
DOI: 10.1262/jrd.2012-126
|View full text |Cite
|
Sign up to set email alerts
|

Selection of <i>In Vitro</i>-Matured Porcine Oocytes Based on Localization Patterns of Lipid Droplets to Evaluate Developmental Competence

Abstract: Localization patterns of lipid droplets in the cytoplasm of porcine oocytes were evaluated as a novel marker for in vitro maturation (IVM) of oocytes with high developmental competence. Porcine oocytes were cultured in TCM-199, which is a complete synthetic medium, for 44 h at 38.5 C. Localization patterns were divided into 2 classes: lipid droplets localized uniformly in the whole cytoplasm (class I) and those that were centrally located (class II). After IVM in TCM-199, 60% of matured oocytes exhibited the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…As highlighted in previous study [26], the higher lipid content of BCB + bovine oocytes provides a cellular and functional basis for their greater developmental competence. If this is the case, one could speculate that the lipid content not only affects oocyte competence [25,27,28] but also might be an estimation of G6PDH-activity as previously shown in bovine oocytes [26]. However, to the best of our knowledge, no previous study has reported on the association between the content of cytoplasmic lipid and developmental competence of oocytes to further support early embryonic development and activity of the G6PDH enzyme.…”
Section: Introductionmentioning
confidence: 69%
“…As highlighted in previous study [26], the higher lipid content of BCB + bovine oocytes provides a cellular and functional basis for their greater developmental competence. If this is the case, one could speculate that the lipid content not only affects oocyte competence [25,27,28] but also might be an estimation of G6PDH-activity as previously shown in bovine oocytes [26]. However, to the best of our knowledge, no previous study has reported on the association between the content of cytoplasmic lipid and developmental competence of oocytes to further support early embryonic development and activity of the G6PDH enzyme.…”
Section: Introductionmentioning
confidence: 69%
“…Additionally, GM-CSF reversed the beneficial effects of pFF when combined in IVMM. In the method article, Hiraga used a non-supplemented TFF medium, or TCM with serum, similar to the only pFF supplemented group in this study 29 . From 2013, there were no new studies have evaluated the distribution of lipid droplets after IVM.…”
Section: Discussionmentioning
confidence: 99%
“…The oocytes were evaluated by the method of Hiraga K. et al (2013) with some modifications 29 . Briefly, with the micromanipulation system, the denuded oocytes were observed with an inverted microscope and classified into two groups according to the localization patterns of lipid droplets.…”
Section: Assessment Of Lipid Droplet Localizationmentioning
confidence: 99%
“…The COCs were matured with 10 IU/mL of gonadotropin hormone, pregnant mare serum gonadotropin (Lee Biosolutions, Maryland Heights, MO, USA), and human chorionic gonadotropin for the first 22 h. After the maturation, cumulus cells were removed from the oocytes with hyaluronidase. Class Ⅱ oocytes were selected for further experiments [ 45 ]. Fresh semen with high viability and motility was delivered every week from Darby Genetics Inc. (Anseong, Gyeonggi-do, Korea).…”
Section: Methodsmentioning
confidence: 99%